Practical colorimetry of 3-Nitro-1,2,4-Triazol-5-One - Tennant, Mat; Chew, Siao Chien; Krämer, Tobias; Mai, Nathalie; McAteer, Daniel; Pons, Jean-François (Wiley, 2018)
A field ready colorimetric method of quantifying the concentration of aqueous 3‐nitro‐1,2,4‐triazol‐5‐one (NTO), several orders of magnitude below its environmental toxicity level, has been developed. The test allows for the immediate evaluation of the level of contamination in aqueous solution without the need for analytical equipment such as high pressure liquid chromatography (HPLC). The observed colours have been explained by the different NTO species present over the range of pH; these observations are supported by modelling and experimental results.